MONICET: The Azores whale watching contribution to cetacean monitoring - González García, Laura (2023)
ABSTRACT: The Azores islands have been historically linked to cetaceans, becoming an example of a successful transition from whaling to whale watching. Twenty-eight cetacean species have been sighted in these waters, making the archipelago one of the most recognised whale and dolphin watching destinations worldwide. The business is well-established in the region, operates in four of the nine islands year-round or seasonally and provides an excellent opportunity to collect long term information on cetacean distribution and abundance in an affordable way. Continuous monitoring is indeed essential to establish baseline knowledge and to evaluate cetacean response to potential natural or anthropogenic impacts. Opportunistic data greatly complement traditional dedicated surveys, providing additional support for appropriate management plans.